Plasmodium falciparum msp2 Genotypes and Multiplicity of Infections among Children under Five Years with Uncomplicated Malaria in Kibaha, Tanzania - W. Kidima; G. Nkwengulila (Journal of Parasitology Research)
Genetic diversity of Plasmodium falciparum may pose challenges in malaria treatment and prevention through chemotherapy and vaccination. We assessed Plasmodium falciparum genetic diversity and multiplicity of infection (MOI) of P. falciparum infections and sort relationship of parasitaemia with P. falciparum msp2 genotypes as well as with the number of infecting clones. The study was carried out in Kibaha, Tanzania. Ninety-nine children under five years with uncomplicated malaria were recruited. Genetic diversity was analyzed by genotyping the msp2 gene using PCR-Restriction Fragment Length Polymorphism. Thirty-two different msp2 alleles were obtained. The msp2 3D7 allelic frequency was higher (48.1%) and more prevalent than FC27 (27.3%) (p<0.05). Twenty-four percent of the infections were mixed alleles. The individuals with FC27 had high parasitemia compared to those with 3D7 alleles (p=0.038). The mean MOI was low (1.4 clones, 95% CI 1.2–1.5). The P. falciparum population among children at Kibaha is composed of distinct P. falciparum clones, and parasites having 3D7 are more frequent than those with FC27 alleles. Individuals with parasite having FC27 alleles have high parasite densities suggesting that parasites with FC27 alleles may associate with severity of disease in Kibaha. Low MOI at Kibaha suggests low malaria transmission rate.